The role of guideline organizations in nationwide guideline implementation: a qualitative study - Andrea C. Thoonsen; Hanneke Merten; Toby T. Broeders; Anika Gans; Ilse van Beusekom; Diana M. J. Delnoij; Martine C. de Bruijne (Health Research Policy and Systems)
Abstract Background Research indicates suboptimal uptake and impact of clinical practice guidelines in Dutch healthcare. Dutch guideline organizations, i.e. guideline developers, governmental agencies, health insurers and other national organizations, develop, authorize and/or support the use of guidelines in Dutch clinical practice. These organizations influence the end users’ awareness, accessibility, understanding, acceptability and applicability of guidelines and, therefore, play a crucial role in guideline implementation. This study explores how they plan, execute, monitor and evaluate guideline dissemination and implementation. Methods Utilizing a qualitative design, we conducted semi-structured interviews with 35 participants from 24 guideline organizations. We conducted framework analysis, using theories on guideline implementation planning, the ‘taxonomy of strategies for achieving guideline implementation and compliance’ and the principles of logic models to analyse the data. Results Most guideline organizations made limited use of implementation planning approaches that are known to enhance guideline uptake and impact. These approaches include pre-identifying implementation barriers, engaging stakeholders and applying implementation theories, models and frameworks to select and tailor implementation strategies. Instead, they primarily relied on a standard set of predominantly dissemination and occasional implementation strategies known to be practical in terms of ease, cost and time. Commonly used implementation strategies included distributing, advertising and presenting guideline materials, along with providing additional implementation supporting materials. Regarding monitoring and evaluation methods, few organizations assessed the process, outcome or impact of guideline implementation. Those that did primarily relied on clinical peer review and benchmark information for their assessments. Conclusions While Dutch guideline organizations recognized and endorsed the importance of implementation, this did not consistently translate into tailored implementation actions. Most guideline organizations did not have an integrated, structural and well-thought-out plan for implementation. The lack of regular, structured monitoring and evaluation raised uncertainties about the effectiveness of implementation in supporting end users and improving patient outcomes. Suggested follow-up research and practice enhancements could strengthen central-level implementation efforts, fostering more effective local implementation and, ultimately, improving health outcomes.